Water tariffs as a determinant for water consumption: The analysis across polish cities - Krzysztof Berbeka (Economic and Environmental Studies (E&ES), 2017)
This paper presents an empirical verification of the demand price elasticity for piped water in major cities in Poland - it was the main goal of the research. The information concerning the demand reaction to price changes is substantial for sustainable urban water demand. Any prediction of possible adaptation to global climate change also requires detailed information about consumer behaviour related to water consumption. This study was conducted on panel data consisting of approx. 100 largest Polish cities over the period of 5 years: 2010-2014. It was the second analysis in Poland and the first conducted on individual data from Polish agglomerations, instead of aggregated data for the whole country. Such detailed level of disaggregation has also some disadvantages - due to the lack of income data for each city - the income elasticity was skipped in the model. Finally the results were in the same range as figures obtained in other EU countries.
Keywords: C54; D12; E39; H40; H44; Q25; Q53; 330; water consumption; water demand price elasticity